2014
DOI: 10.1519/jsc.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Time Interval Moderates the Relationship Between Psyching-up and Actual Sprint Performance

Abstract: Hammoudi-Nassib, S, Chtara, M, Nassib, S, Briki, W, Hammoudi-Riahi, S, Tod, D, and Chamari, K. Time interval moderates the relationship between psyching-up and actual sprint performance. J Strength Cond Res XX(X): 000-000, 2014-This study attempted to test whether the strongest effect of psyching-up (PU) strategy on actual sprint performance can be observed when the strategy is used immediately (or almost) before performance compared with when there is a delay between PU and performance. To do so, 16 male spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This sustainably beneficial impact of VMBR intervention regime on the Thirty Mt. Dash performance, got evidentially supported by several previous research investigations 45,58,[65][66][67] . As Silmani and the coresearchers 67 conducting an extensive systematic review on impacts of differential types of visualization techniques earlier pointed out and confirmed positive role of visualization on increment in Thirty Mt.…”
Section: Open Access Abstractsupporting
confidence: 80%
See 3 more Smart Citations
“…This sustainably beneficial impact of VMBR intervention regime on the Thirty Mt. Dash performance, got evidentially supported by several previous research investigations 45,58,[65][66][67] . As Silmani and the coresearchers 67 conducting an extensive systematic review on impacts of differential types of visualization techniques earlier pointed out and confirmed positive role of visualization on increment in Thirty Mt.…”
Section: Open Access Abstractsupporting
confidence: 80%
“…As Silmani and the coresearchers 67 conducting an extensive systematic review on impacts of differential types of visualization techniques earlier pointed out and confirmed positive role of visualization on increment in Thirty Mt. Dash performance 45,65,66 .…”
Section: Open Access Abstractmentioning
confidence: 76%
See 2 more Smart Citations
“…The absence of a music effect on these variables could be due to the fact that the participants listened to music while warming-up and not while performing the task. In accordance with this suggestion, authors [ 32 ] have recently shown that the greater the time interval after the use of a mental strategy, the lower the impact of this strategy on STMP.…”
Section: Discussionmentioning
confidence: 63%